Processing Coconut (Cocos Nucifera L.) into Virgin Coconut Oil Products: Cold-press Method - Peter Dekker; Hanny Frederik; Ivan Th. J. Weismann (Sekolah Tinggi Teologi Levinus Rumaseb Sentani, Papua, 2023)
This article will describe the impact producing and using Virgin Coconut Oil can make on the life of people in a small village. It offers them work opportunities and a better income for the farmers, but it also helps them become healthier. It has a reason why people worldwide described the Coconut as the “fruit of life”. The method is a literature review and describes the processing of Virgin Coconut Oil located in Takalar, South Sulawesi, Indonesia. Sulalam's VCO has a good impact on body health and for maintaining health.